Intelligent stick / Mohamad Ridzuan Hashim, Mohd Rusydi Zahari and Muhammad Nur Shafiq Kamaruddin - Hashim, Mohamad Ridzuan; Zahari, Mohd Rusydi; Kamaruddin, Muhammad Nur Shafiq (2013)
The main purpose of this project is to constrict the problems to the blind people when they walking or doing activities .In order to make it into reality, many initiative that have been taken nowadays to upgrade the safety of a stick that used by the blind people .This is where the project called the “Intelligent Stick” is developed with a complete system that is function to give signal to the owner of the stick if having dangerous obstacle near them like drain or big hole .When the ultrasonic sensor used is opened ,it will send a signal to the PIC. The PIC will then command the buzzer and the vibration motor to directly notify the owner. From this, the owner will know and notice about obstacles that are near them while walking to take immediate action.